PERSEPSI MASYARAKAT AKAN PENTINGNYA KEBERADAAN LEMBAGA KEUANGAN MIKRO DI DESA PEMECUTAN KELOD - Karmini, Ni Luh; Sutrisna, I Ketut (Buletin Studi Ekonomi, 2021)
The objectives of this study are 1) Knowing the community's perception of the existence of a microfinance institution (LKM) in Pemecutan Kelod Village, 2) Describing the factors that hinder the existence of a microfinance institution (LKM) in Pemecutan Kelod Village. The data analysis used in this research is descriptive qualitative analysis, which is research that aims to accurately describe the properties of an object, condition, symptom or group to determine the frequency of the relationship or influence between a symptom and other symptoms in society. Its purpose is to create a systematic picture. Based on the results of the study, it can be concluded that the community states the importance of the existence of microfinance institutions to improve the community's economy and requires experienced, properly educated and honest managers. The suggestion conveyed in this research is that it is necessary to initiate the establishment of a microfinance institution in the banjar in Pemecutan Kelod Village and to recruit experienced, educated and honest managers so that they are trusted by the community.